DAYA SAING DESTINASI WISATA KAMPA, TUMBURANO, DAN WATUNTINAPI BERBASIS SPASIAL DI KABUPATEN KONAWE KEPULAUAN - Mukhayar Mukhayar; Yulius Barra Pasolon; Laode Muhammad Golok Jaya (Universitas Halu Oleo, 2019)
The purpose of the research is 1) identify the actual condition of the competitiveness of Kampa, Tumburano and Watuntinapi tourist destinations. 2) formulating priority scale of competitiveness development among Kampa, Tumburano and Watuntinapi tourism destinations. In the development of the tourism sector in particular, the Konawe Kepulauan regional government has synchronized Kampa, Tumburano and Watuntinapi tourism destinations as Kanopi tourist destinations. These three tourist destinations are the focus of the development of the Konawe Kepulauan regional government. This research was conducted descriptively qualitative and quantitative with spatial methods and analytical hierarchy process (AHP). Based on the results of the study concluded that the actual condition of competitiveness between Kampa tourism destinations, Tumburano tourist destinations, and Watuntinapi tourist destinations that are incorporated in the acronym Kanopi, surpassed by Kampa tourist destinations. Whereas the priority scale for developing the competitiveness of tourist destinations incorporated in the Kanopi acronym is Kampa tourism destinations as the main priority, then followed by Tumburano turism destination, and last Watuntinapi tourist destination Keywords: AHP, tourist destination competitiveness, Kampa, spatial, Tumburano, Watuntinapi